Augmented Reality in Indonesia's Primary School: Systematic Mapping Study - Dian Syafitri Chani Saputri; Dyah Susilowati (International Journal of Engineering and Computer Science Applications (IJECSA), 2022)
Augmented reality is an increase trending technology in education. Research in the field of AR for Education is increasing every year. A large number of research reviews have focused on the use of AR in education worldwide and at all levels of education, but there have not been many reviews of the use of AR at the elementary school level in Indonesia. This study aims to determine the trends of using AR in elementary school in Indonesia. This research used a Systematic Mapping Study approach, which consists of the stages of definition research question, conduct research, screening papers, keywording using abstract, and data extraction and mapping process. Subjects of elementary education, grade, type of AR application, and research method and facets, have been used in classifying AR. Inclusion and exclusion criteria were used in determining the relevant papers. This study examining 42 articles containing “augmented reality”, “elementary school” and “Indonesia” in their titles, abstracts, and keywords. Articles were published between 2017 and 2021. The results have shown that science learning is the most subject to be the object of AR research, followed by mathematics, language, and culture. Most of the AR implementations are implemented in class IV, V and VI. The most widely used type of AR application is marker-based AR. The most widely used research method is R&D which focuses on developing AR products.